Stroke in Pregnancy and Preeclampsia: Effect of Low‐Dose Aspirin Treatment on Collateral Flow Velocity and Cerebral Blood Flow Autoregulation During Ischemia in Rats - Marilyn J. Cipolla; Sarah M. Tremble (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease)
Background Experimental preeclampsia (ePE) has been shown to have worsened outcome from stroke. We investigated the effect of low‐dose aspirin, known to prevent preeclampsia, on stroke hemodynamics and outcome, and the association between the vasoconstrictor and vasodilator cyclooxygenase products thromboxane A2 and prostacyclin. Methods and Results Middle cerebral artery occlusion was performed for 3 hours with 1 hour of reperfusion in normal pregnant rats on day 20 of gestation and compared with ePE treated with vehicle or low‐dose aspirin (1.5 mg/kg per day). Multisite laser Doppler was used to measure changes in cerebral blood flow to the core middle cerebral artery and collateral vascular territories. After 30 minutes occlusion, phenylephrine was infused to increase blood pressure and assess cerebral blood flow autoregulation. Infarct and edema were measured using 2,3,5‐triphenyltetrazolium chloride staining. Plasma levels of thromboxane A2, prostacyclin, and inflammatory markers in plasma and cyclooxygenase levels in cerebral arteries were measured. ePE had increased infarction compared with normal pregnant rats (P<0.05) that was reduced by aspirin (P<0.001). ePE also had intact cerebral blood flow autoregulation and reduced collateral perfusion during induced hypertension that was also prevented by aspirin. Aspirin increased prostacyclin in ePE (P<0.05) without reducing thromboxane B2, metabolite of thromboxane A2, or 8‐isoprostane‐prostaglandin‐2α, a marker of lipid peroxidation. There were no differences in cyclooxygenase levels in cerebral arteries between groups. Conclusions Low‐dose aspirin in ePE reduced infarction that was associated with increased vasodilator prostacyclin and improved collateral perfusion during induced hypertension. The beneficial effect of aspirin on the brain and cerebral circulation is likely multifactorial and worth further study.